Konsep Peserta Didik Dalam Pemikiran Abdul Wahid Hasyim - Samsul Haq; Maragustam Siregar (Jurnal Shaf, 2024)
This research aims to explore the concept of learners, the values and principles underlying the concept of learners and the role of learners in the educational process in the thought of Abdul Wahid Hasyim. This research is a library research using a descriptive qualitative approach with documentation data collection techniques and data analysis using Milles and Huberman analysis techniques. The concept of learners thought Abdul Wahid Hasyim: 1) Individuals have unique potential and should be developed holistically including intellectual, moral, spiritual, and social aspects. 2) The importance of education as a means to prepare students to become responsible individuals and contribute positively to society. 3) Teaching Islamic values as a moral and spiritual foundation for education as an integral part of the learning process. 4) The importance of equality in education, regardless of social or economic background, has the same right to gain access and benefit from education. The values of the concept of learners thought Abdul Wahid Hasyim: 1) Humanity and Justice, 2) Character Building and Morality, 3) Independence and Responsibility, 4) Religion and Spirituality, and 5) Creativity and Innovation. The role of learners: 1) Active Subject in Learning, 2) Development of Individual Potential, 3) Responsibility in Learning, 4) Character and Personality Building, and 5) Collaborative Teacher-Learner Relationship. The relevance of Abdul Wahid Hasyim's concept of learners in the context of modern education: 1) Holistic Approach in Education, 2) Active Involvement of Learners in Learning, 3) Character and Morality Building, 4) Equality in Access and Educational Opportunities and 5) Development of Creativity and Innovation.